Frontispiece: Effect of Site‐Specific O‐Glycosylation on the Structural Behavior of NOTCH1 Receptor Extracellular EGF‐like Domains 11 and 10. Issue 54 (25th September 2020) - Yokoi, Yasuhiro; Nishimura, Shin‐Ichiro
Abstract : Human NOTCH1 receptor contains 36 epidermal growth factor (EGF)‐like repeating domains, in which O ‐glycosylation status of the EGF12 domain regulates the interaction with Notch ligands. In their Full Paper on page 12363 ff., Y. Yokoi and S.‐I. Nishimura carried out chemical synthesis and NMR studies of site‐specifically O ‐glycosylated EGF11 and EGF10. Four EGF11 and five EGF10 modules were synthesized. The specific O ‐glycosylation states affected in vitro folding of EGF10 more than EGF11, while calcium ion had a larger effect on EGF11 folding. Comprehensive NMR studies shed light on the new type "sugar bridges" crosslinking Thr‐ O ‐GlcNAc in the consensus sequence C5‐X‐X‐G‐X‐(T/S)‐G‐X‐X‐C6 and an amino acid in the hinge region between the domains, 445Thr‐ O ‐GlcNAc—IIe451 in domain 11 and 405Thr‐ O ‐GlcNAc—Gln411 in domain 10.